(3UdI GdPGcQjf hSgh GdZGadjfs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg fSJYjfg hfSJTgO Hg hfSJZaQg hfYhP HGddg ef CTQGQ CfaSfG hSjFGJ CYeGdfG ef jgO Gddg adG eVd dg hef jVdd Gddg adG gGOj dgs
(3BNQgG (B:s
(3abdJ dg(B: (3efce HOC GdYde hEdjce jYhO hCfJe Cgd GdhUjI hGdhdGjI aTcQhfj Ydi Pdc hgPG eG GfJgi EdjfG ef eSGFd GdTjN CHG MGRe (B((3cPG(B) (3Ydi GdJeGe hGdceGd hGdMeO ddg hMOgs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs